A Jesuit in the Forbidden City : Matteo Ricci 1552–1610 by R. Po-Chia Hsia (Review) - Cope, Kevin L. (2020)
Untouched by the innovations of modernist authors, most writers of scholarly prose present a conveniently linear world where cause precedes effect and where abundance yields to organization. Multidimensional phenomena of complex personalities decompose into bits and pieces that, in turn, may be evaluated sequentially. Despite all the trendy chatter about innovative, multilevel pedagogies, academic discourse remains remarkably straightforward and flat. Cinema, television, and other visually deep media, by contrast, routinely deploy multiplicity and confusion. Taking a cue from Renaissance drama, with its perplexing habit of beginning in medias res, contemporary popular media routinely plunge uninformed viewers into simultaneously transpiring scenes, events, and stories in the expectation that dominant themes, issues, and personalities will work themselves into clearer view. It is exactly this strategy that R. Po-Chia Hsia follows in A Jesuit in the Forbidden City: Matteo Ricci 1552–1610, a magisterial travelogue-biography in which the central figure, the son of an ambitious bourgeois pharmacist who literally made good by doing holy deeds in hostile environments, keeps emerging, again and again, from a slightly uncanny background of strange, exotic, colorful, frightening, shadowy, and, always, cinematic events.